Desalination and Treatment of Oilfield Produced Waters - Giovanni Campisi; Alice Sorrenti; Paulo B. Mofatto; Alessandro Cosenza; Serena Randazzo; Santo F. Corsino; Marco Capodici; Michele Torregrossa; Alessandro Tamburini; Giorgio Micale (Chemical Engineering Transactions)
Produced water is a salty and organic-polluted byproduct drilled out during the oil extraction. An annual production of 11.2 million of m3 is estimated, based on the production of at least 3 barrels of PW for every barrel of oil extracted. The composition changes according to the well characteristics and to the addition of chemicals during the extraction process. Generally, a high salinity (up to 300 g L-1), due to the contact with subsurface rocks, is observed together with a large amount of dissolved hydrocarbon compound contaminants. Thus, their treatment could be designed on case-by-case basis through tailored studies and experimental investigations as it is not possible to standardize the characteristics of PW. In this work, an innovative PWs treatment scheme is proposed where an Assisted Reverse Electrodialysis (ARED) unit and a Sequencing Batch Moving Bed Biofilm Reactor (SBMBBR) were coupled: ARED is used to reduce the PWs salinity to values lower than 20 g L-1 of NaCl to let the stream compatible with the downstream biologic treatment, where the organic content is reduced ensuring compliance with legislative disposal limits. The desalination was performed under current-control mode and the ARED required less than 2 kWh·m-3PW for reaching the target outlet concentration. The organic content in SBMBBR successfully decreased, showing a Total Organic Carbon (TOC) abatement of about 80%.